FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN HERNIA INGUINAL DEWASA DI RSUD LABUHAN HALMAHERA SELATAN - Hidayat, Ferdian; Husen, Abd Hakim (NHM PRESS, 2023)
Inguinal Hernia disease begins due to the protrusion of an organ, tissue or structure through the wall of the cavity which normally contains these parts through the internal/lateral inguinal annulus tracing the inguinal canal and exiting the abdominal cavity through the external/medial inguinal annulus. This study aims to determine factors related to the incidence of adult inguinal hernias at Labuha Hospital, South Halmahera. This type of research is a case control design. The research sample was 46 respondents (23 cases and 23 controls) taken using the Accidental Sampling technique. Using the Chi-square test with a 95% confidence level. The research results show that the incidence of inguinal hernias in adults has risk factors such as obesity with an OR value = 16,923, work with an OR value = 12,960, chronic cough with an OR value = 110,250 and constipation with an OR value = 44,444.